Prevalence of skin diseases in women with endometriosis: a cross-sectional study - Sakiyama, Paula Hitomi; Castro, Caio Cesar Silva de; Marchioro, Helena Zenedin; Gobo, Cristiane Gisselda; Linhares, Filipe Silva; Miot, Hélio Amante [UNESP] (Wolters Kluwer, 2025)
Endometriosis is a chronic estrogen-dependent disorder with unclear pathogenesis, although the immune system and inflammatory response are directly involved in its development. Despite the increasing population prevalence of endometriosis in modern times and its potential shared pathophysiological mechanisms with some dermatoses associated with immunological, inflammatory, and hormonal factors, to date, no study has investigated the co-occurrence of endometriosis and inflammatory dermatoses. A cross-sectional study was conducted by including 835 adults with endometriosis, recruited from Internet groups, and by nonrandom sampling at a gynecology outpatient clinic; 39 were interviewed in person. As a comparison group, we included 309 women selected among patients who consecutively attended the gynecology clinic due to other complaints, companions in consultations, and employees of the hospital. The participants were asked about current dermatoses (self-reported on the Internet and confirmed by a dermatologist in the endometriosis subjects interviewed in person, and in the whole comparison group). Chronic urticaria, alopecia areata, and psoriasis were more prevalent in individuals with endometriosis, compared with women without the disease. The co-occurrence of endometriosis and these inflammatory skin diseases highlights the importance of recognizing associated comorbidities and providing comprehensive care for the overall health of these patients.
Prevalence of skin diseases in women with endometriosis: a cross-sectional study
Keywords: Alopecia areata; Chronic urticaria; Endometriosis; Psoriasis; Skin diseases; Urticária; Endometriose; Psoríase; Pele - Doenças; Alopecia em áreas